2000
DOI: 10.1021/es991251e
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Uranium Compounds in High Ionic Strength Brine by a Halophilic Bacterium under Denitrifying Conditions

Abstract: We investigated the transformations of uranyl nitrate, uranyl citrate, uranyl ethylenediaminetetraacetate (U-EDTA), and uranyl carbonate by a denitrifying halophilic bacterium, Halomonas sp. (WIPP1A), isolated from the Waste Isolation Pilot Plant (WIPP) repository. The addition of uranyl nitrate, uranyl citrate, or uranyl EDTA to the brine or bacterial growth medium resulted in the precipitation of uranium. Extended X-ray absorption fine structure (EXAFS) analysis of the precipitates formed in the brine and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 18 publications
3
26
1
Order By: Relevance
“…So, it can be concluded that maximum lead biosorption by MWS occured at pH 6. Similar results of optimum pH for lead binding by various sorbents have been reported [7,11,22,23].…”
Section: Effect Of Phsupporting
confidence: 85%
“…So, it can be concluded that maximum lead biosorption by MWS occured at pH 6. Similar results of optimum pH for lead binding by various sorbents have been reported [7,11,22,23].…”
Section: Effect Of Phsupporting
confidence: 85%
“…However, some Halomonas spp., including H. maura, are capable of anoxic respiration under nitrate reducing conditions (Aragandoña et al 2006;Llamas et al 2006;Peyton et al 2001). Previous studies have utilized Halomonas isolates to study metal-microbe interactions under anoxic conditions (Francis et al 2000;Khijniak et al 2003), although Cr(VI) reduction by a Halomonas isolate has not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…To simulate a carbonatedominated geochemical condition, a stock solution composed predominantly of uranyl carbonate complexes was prepared by the addition of a 1/10th volume of saturated ammonium carbonate to a 100 mM uranyl nitrate hexahydrate stock solution (final U concentration, 89 mM; carbonate concentration, 214 mM) (32,35,36). The formation of carbonate complexes with U was verified by monitoring the absorption spectra of solution in the visible light range between 400 and 500 nm (UV Unicam 300; Thermo Scientific) with specific peaks at 434 nm, 448 nm, and 464 nm (35,36 ammonium carbonate, as explained above; final pH, 9.0). The concentration of carbonate in GC2 in all assays was always 2.4-fold higher than the U concentration used; i.e., the carbonate-to-U ratio of 2.4 was always maintained.…”
Section: Methodsmentioning
confidence: 99%